Prevalence of Temporomandibular Disorder (TMD) in Special Region of Yogyakarta Archery Athletes - Arief Waskitho; Dhea Aleyda Muthmainnah (Odonto : Dental Journal, 2026)
Background: The temporomandibular joint (TMJ) is an important component of the masticatory and stomatognatic system, responsible for opening and closing the mouth, chewing food, and breathing. Anchoring, which refers to the hand placement on the chin, can lead to dysfunction of the TMJ known as temporomandibular disorder (TMD) Method: This study utilized a descriptive observational approach with a cross-sectional design. It was conducted in various archery fields involving 57 respondents. The examination used the ID-TMD index. Result: Out of  57 respondents, 28 (49,13%) experienced symptoms of TMD: 45.61% experienced mild TMD, and 3,50% experienced moderate TMD. Adolescent women are the group that complains most about TMD, with the most common symptom being headache, which is felt by 77,19% of all respondents. Conclusion: There is a tendency that the anchoring position is associated with the occurrence of TMD among archery athletes, as indicated by the ID-TMD index.